Long-Acting Lipoglycopeptides: "Lineless Antibiotics" for Serious Infections in Persons Who Use Drugs. (5th June 2019) - Morrisette, Taylor; Miller, Matthew A; Montague, Brian T; Barber, Gerard R; McQueen, R Brett; Krsak, Martin
Abstract: Background: Injection drug use is associated with serious infections. Due to challenges with medical management of addiction, relapses and additional infections are common. Persons who use drugs (PWUD) are more likely to leave against medical advice before completing treatment, which could result in treatment failure. Prolonged intravenous (IV) antimicrobial therapy in PWUD may be complicated by concern for IV catheter misuse, sometimes requiring prolonged hospitalization. Ideal alternatives would provide the following: (1) high success rate; (2) reduced rate of medical complications; (3) improved safety profiles; and (4) improved cost-effectiveness. Long-acting lipoglycopeptides present such opportunity for treatment of serious Gram-positive infections. Methods: We performed a system-wide, retrospective analysis of adults admitted to University of Colorado Health from September 2015 to June 2018 and treated with dalbavancin or oritavancin based on clinical judgment of their treating physicians. Results: Fifty-six patients met inclusion criteria (17 PWUD vs 39 non-PWUD). The PWUD group were younger, healthier by Charlson comorbidity index, more likely insured by Medicaid, and admitted for conditions requiring longer treatment. Ten patients were lost to follow-up. Of the patients with follow-up, clinical failure was met in 1 PWUD patient (6%) and 6 non-PWUD patients (15%) ( P = .413). The median hospital length-of-stay reduction was 20 days (interquartile range [IQR], 10–30 days) in PWUD vs 11 days (IQR, 9–14 days) in non-PWUD; P = .133. Estimated median savings were $40 455.08 (IQR, $20 900.00–$62 700.00) in PWUD vs $19 555.08 (IQR, $15 375.08–$23 735.08) in non-PWUD; P = .065. Conclusions: Long-acting lipoglycopeptides may be equally effective as standard-of-care, present a safety advantage, and secure earlier discharge and significant cost-savings.